1989
DOI: 10.1002/dev.420220206
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive behaviors in adult rats deprived of playfighting experience as juveniles

Abstract: Matched litter mates were reared in one of three conditions: in pairs or in isolation with or without one hour of daily playfighting experience from 20 to 50 days of age. The rats were then regrouped within condition so that they lived with identically reared cagemates for a month. This regrouping eliminated the transient effects of isolation such as increased fearfulness. When tested as adults, there was no effect of early rearing condition on the probability of intraspecific aggression or muricide, although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
2
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 39 publications
(33 reference statements)
2
71
2
2
Order By: Relevance
“…Since social experiences early in life shape brain development and adult behavior (Champagne and Curley, 2005;Hol et al, 1999;Potegal and Einon, 1989;van den Berg et al, 1999a;van den Berg et al, 1999b), changes in the social repertoire caused by drug use during adolescence may have profound, long-lasting behavioral effects. Our results also suggest a role for anandamide in psychopathological disorders associated with social dysfunctions, such as autism and schizophrenia, and extend the potential therapeutic utility of indirect cannabinoid agonists, such as URB597, to these disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since social experiences early in life shape brain development and adult behavior (Champagne and Curley, 2005;Hol et al, 1999;Potegal and Einon, 1989;van den Berg et al, 1999a;van den Berg et al, 1999b), changes in the social repertoire caused by drug use during adolescence may have profound, long-lasting behavioral effects. Our results also suggest a role for anandamide in psychopathological disorders associated with social dysfunctions, such as autism and schizophrenia, and extend the potential therapeutic utility of indirect cannabinoid agonists, such as URB597, to these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, social play takes plenty of time and energy, and evolution demands that activities costing energy provide survival value in return. It has been suggested that, by varying, repeating, and/or recombining subsequences of behavior outside their primary context, play serves to develop physical, cognitive and social capacities, and especially to acquire the ability to flexibly use these capacities under changeable circumstances (Fagen, 1981;Špinka et al, 2001) The notion that social play is important for development is supported by the observations that rats housed in isolation during adolescence, when social play behavior is most abundant, show a variety of behavioral impairments during adulthood (Hol et al, 1999;Potegal and Einon, 1989;van den Berg et al, 1999a;van den Berg et al, 1999b). However, despite its importance for behavioral development, the neural substrates of social play are incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Play as an early mental activity Play appears to be present in the development of all young mammals because it has a key role in our learning to recognize and interpret social signals and the affective states of others (Brown, 2009;Slade, 1987), regulate aggression, and respond effectively in interpersonal contexts (Pellegrini & Smith, 2005;Potegal & Einon, 1989). From a neurocognitive perspective, play contributes to the development of higher cognitive functions and of the prefrontal regions implicated in inhibition and executive control that underlie creative, self-reflective, and empathic capabilities (Panksepp, 2007).…”
Section: Mentalization and Reflective Functioningmentioning
confidence: 99%
“…Play is now known to promote affectively beneficial gene expression profiles (Burgdorf, Kroes, Beinfeld, Panksepp, & Moskal, 2010), brain development (Gordon, Kollack-Walker, Akil, & Panksepp, 2002;Gordon, Burke, -xxAkil, Watson, & Panksepp, 2003;Panksepp, 2007;van den Berg et al, 1999), and emotion regulation development van den Berg et al, 1999). Mammals who are deficient in play have difficulty regulating aggressive urges (Potegal & Einon, 1989). Those with little play experience early in life have altered social, sexual, and conflict interactions with peers (van den Berg et al, 1999).…”
Section: Playmentioning
confidence: 99%